2013
DOI: 10.4028/www.scientific.net/msf.762.183
|View full text |Cite
|
Sign up to set email alerts
|

Young's Modulus Profile in Kolsterized AISI 316L Steel

Abstract: AISI 316L steel, subjected to a low temperature carburizing treatment (kolstering), has been examined by Mechanical Spectroscopy (MS) and nanoindentation to determine the Youngs modulus of the surface hardened layer (S phase). MS results showed that the average value of elastic modulus of S phase is 202 GPa, a little higher than that of the untreated material.Nanoindentation tests, carried out with loads of 5, 15 and 30 mN, evidence a modulus profile vs depth: E is ~ 400 GPa at a distance from the surface of ~… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 17 publications
(17 reference statements)
4
15
1
1
Order By: Relevance
“…More details of the nanoindentation test are discussed by Bocchini et al in [31]. During the test, the nanoindenter records the penetration depth h and the load w. The slope dw/dh of the unloading curve at the beginning of unloading can be used to measure E as described by Fougere et al [32], Chen et al [33], and Balijepalli et al [34,35]. Chen et al in [33] showed a typical nanoindentation test load-indentation depth curve, and the author explained how it is possible to calculate the plasticity factor η p , defined as the ratio of plastic deformation work to total deformation work.…”
Section: Methodsmentioning
confidence: 99%
“…More details of the nanoindentation test are discussed by Bocchini et al in [31]. During the test, the nanoindenter records the penetration depth h and the load w. The slope dw/dh of the unloading curve at the beginning of unloading can be used to measure E as described by Fougere et al [32], Chen et al [33], and Balijepalli et al [34,35]. Chen et al in [33] showed a typical nanoindentation test load-indentation depth curve, and the author explained how it is possible to calculate the plasticity factor η p , defined as the ratio of plastic deformation work to total deformation work.…”
Section: Methodsmentioning
confidence: 99%
“…More details of the nanoindentation test are discussed by Bocchini et al in [31]. During the test, the nanoindenter records the penetration depth h and the load w. The slope dw/dh of the unloading curve at the beginning of unloading can be used to measure E as described by Fougere et al [32], Chen et al [33], and Balijepalli et al [34,35]. Chen et al in [33] showed a typical nanoindentation test load-indentation depth curve, and the author explained how it is possible to calculate the plasticity factor ηp, defined as the ratio of plastic deformation work to total deformation work.…”
Section: Methodsmentioning
confidence: 99%
“…are not so critical for the results. However, the FIMEC technique has failed in testing materials with thin coatings or surface layers (e.g., kolsterized stainless steels [29][30][31], nitrided and nitrocarburized steels [32,33]), where the penetration depth is larger than the 100 µm thicknesses of the surface layers. Failure has also been reported in testing welding seams made through such high energy sources as laser and electron beam, where the diameter of the imprint is larger than the MZ widths [34].…”
Section: Materials and Experimental Proceduresmentioning
confidence: 99%